Further evidence from common garden rearing experiments of heritable traits separating lean and siscowet lake charr (Salvelinus namaycush) ecotypes. Issue 12 (19th May 2022) - Euclide, Peter T.; Jasonowicz, Andrew; Sitar, Shawn P.; Fischer, G. J.; Goetz, Frederick W.
Abstract: Genetic evidence of selection for complex and polygenically regulated phenotypes can easily become masked by neutral population genetic structure and phenotypic plasticity. Without direct evidence of genotype‐phenotype associations it can be difficult to conclude to what degree a phenotype is heritable or a product of environment. Common garden laboratory studies control for environmental stochasticity and help to determine the mechanism that regulate traits. Here we assess lipid content, growth, weight, and length variation in full and hybrid F1 crosses of deep and shallow water sympatric lake charr ecotypes reared for nine years in a common garden experiment. Redundancy analysis (RDA) and quantitative‐trait‐loci (QTL) genomic scans are used to identify associations between genotypes at 19, 714 single nucleotide polymorphisms (SNPs) aligned to the lake charr genome and individual phenotypes to determine the role that genetic inheritance plays in ecotype phenotypic diversity. Lipid content, growth, length, and weight differed significantly among lake charr crosses throughout the experiment suggesting that pedigree plays a large roll in lake charr development. Polygenic scores of 15 SNPs putatively associated with lipid content and/or condition factor indicated that ecotype distinguishing traits are polygenically regulated and additive. A QTL identified on chromosome 38 contained >200 genes, some of which were associated with lipid metabolism and growth, demonstrating the complex nature of ecotype diversity. The results of our common garden study further indicate that lake charr ecotypes observed in nature are predetermined at birth and that ecotypes differ fundamentally in lipid metabolism and growth.